Electromyographic Analysis of Lower Limb Muscles During Multi-Joint Eccentric Isokinetic Exercise Using the Eccentron Dynamometer - Brennan J. Thompson; Merrill Ward; Brayden Worley; Talin Louder (Applied Sciences)
Eccentric muscle actions are integral to human movement, rehabilitation, and performance training due to their characteristic high force output (overload) and low energy cost and perceived exertion. Despite the growing use of eccentric devices, a gap in the research exists exploring multi-muscle activation profiles during multi-joint eccentric-only, isokinetic exercise. This study aimed to quantify and compare surface electromyographic (EMG) activity of four leg muscles—vastus lateralis (VL), tibialis anterior (TA), biceps femoris (BF), and medial gastrocnemius (GM)—during a standardized (isokinetic) submaximal eccentric multi-joint exercise using the Eccentron dynamometer. Eighteen healthy adults performed eccentric exercise at 40% of their maximal eccentric strength. Surface EMG data were analyzed using root mean square (RMS) and integrated EMG (iEMG) variables. Repeated-measures ANOVAs and effect sizes (ES) were used to evaluate within-subject differences across muscles. Results showed significantly greater activation in the VL compared to all other muscles (p < 0.05; and ES of 1.28–3.17 versus all other muscles), with the TA also demonstrating higher activation than the BF (p < 0.05). The BF exhibited the lowest activation, suggesting limited hamstring engagement. These findings highlight the effectiveness of the multi-joint isokinetic eccentric leg press movement (via an Eccentron machine) in targeting the quadriceps and dorsiflexors, while indicating the possible need for supplementary hamstring and plantar flexor exercises when aiming for a comprehensive lower body training routine. This study provides important insights for optimizing eccentric training protocols and rehabilitation strategies.